Immunoglobulin producing cells in bone marrow and blood of patients with multiple sclerosis and controls. Issue 5 (May 1991) - Fredrikson, S; Baig, S; Link, H
Abstract : Multiple sclerosis (MS) is characterised by intrathecal synthesis of IgG, less frequently of IgA and IgM. Local production of antibodies to myelin basic protein (MBP) and other myelin components has also been reported, and autoimmune pathogenesis has been postulated. Whether MS is accompanied by a systemic B cell response is less clear. To elucidate this question, we examined bone marrow and peripheral blood from patients with MS and controls for cells secreting IgG, IgA and IgM, as well as anti-MBP antibodies of these three isotypes. Patients with MS without any signs of concurrent infections had higher numbers of IgG + IgA + IgM secreting cells both in bone marrow and peripheral blood compared with healthy controls. The same abnormalities were observed in patients with other inflammatory neurological diseases (OIND). When analysing individual isotypes, patients with MS and OIND had higher numbers of IgA secreting cells both in bone marrow and blood compared with healthy controls. Only one of 13 MS patients examined had anti-MBP antibody secreting cells in bone marrow and blood. The systemic B cell response registered in MS is also present in other inflammatory neurological diseases and its specificity and possible role in the pathogenesis of MS remains unknown.